Water quality characteristics in experimental fish ponds, Malaysia. - Md. Yusoff, Fatimah (1990)
Nine earthen ponds were fertilized in three rates. Control ponds received no fertilizer; TSP (triple superphosphate)ponds received 28.8kg P2O5/ha/month; and TSP-urea ponds received 7.1KG p2o5 and 35.5 kg urea/ha/week. Stocking density was 0.5 fish/m2. Weekly measurements of temperature, dissolved oxygen, conductivity, pH, total alkalinity, phosphorus and nitrogen were made. Ponds which received fertilizer input exhibited significantly higher mean oxygen concentrations and fluctuations than the control (p<0.005). Mean pH values were 6.90, 7.50 and 8.50 in control, TSP and TSP-urea treatments, respectively. Diurnal pH change was highest in TSP-urea treatment ponds followed by TSP and control ponds. Means values for total alkalinity were 22.90, 25.7 and 28.2mg CaCO3/1 in control, TSP and TSP-urea ponds respectively. Free CO2 in TSP-urea treatment went below equilibrium carbon dioxide concentrations in late afternoons daily. Nitrogen concentrations were lowest in TSP ponds, but highest in TSP-urea ponds. Total phosphorus concentration in control was significantly lower than than fertilized ponds (p<0.05), but there was no significant difference in orthophosphate concentrations between treatment (p<0.05). Results indicate that fertilization regimes influence water quality of fish ponds.